2017
DOI: 10.1039/c6ce02045c
|View full text |Cite
|
Sign up to set email alerts
|

Stacking interactions between hydrogen-bridged and aromatic rings: study of crystal structures and quantum chemical calculations

Abstract: Please note that technical editing may introduce minor changes to the text and/or graphics, which may alter content. The journal's standard Terms & Conditions and the Ethical guidelines still apply. In no event shall the Royal Society of Chemistry be held responsible for any errors or omissions in this Accepted Manuscript or any consequences arising from the use of any information it contains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 57 publications
4
7
0
Order By: Relevance
“…3) and the potential energy curves (Fig. 7) showed that TTF molecules form the strongest stacking interactions in parallel displaced geometries, which is typical for aromatic rings (Lee et al, 2007;Ninković et al, 2011), most of the chelate rings (Malenov & Zarić, 2018;Malenov et al, 2017) and also hydrogen-bridged rings (Blagojević et al, 2017;Blagojević & Zarić, 2015). The results of quantum chemical calculations are in very good agreement with the data found in the CSD crystal structures, which is well illustrated by similarities of the crystal structures in Fig.…”
Section: Comparing the Geometries In The Csd And Interaction Energiessupporting
confidence: 80%
See 1 more Smart Citation
“…3) and the potential energy curves (Fig. 7) showed that TTF molecules form the strongest stacking interactions in parallel displaced geometries, which is typical for aromatic rings (Lee et al, 2007;Ninković et al, 2011), most of the chelate rings (Malenov & Zarić, 2018;Malenov et al, 2017) and also hydrogen-bridged rings (Blagojević et al, 2017;Blagojević & Zarić, 2015). The results of quantum chemical calculations are in very good agreement with the data found in the CSD crystal structures, which is well illustrated by similarities of the crystal structures in Fig.…”
Section: Comparing the Geometries In The Csd And Interaction Energiessupporting
confidence: 80%
“…At the 4.5 Å offset, the benzenebenzene stacking interaction energy is À2.01 kcal mol À1 and these interactions are highly dominant in crystal structures (Ninković et al, 2011). In addition, the work in our group showed substantial stacking interactions of non-aromatic moieties, such as chelate rings (Malenov & Zarić, 2018;Malenov et al, 2017), cyclohexane (Ninković et al, 2016) and hydrogen-bridged rings (Blagojević et al, 2017;Blagojević & Zarić, 2015). Stacking interactions of all these moieties are comparable in energy with stacking interactions of aromatic molecules and some of them are significantly stronger.…”
Section: Introductionmentioning
confidence: 65%
“…64−68 Blagojevićand Zarićhave performed a systematic analysis to compute stacked hydrogen-bridged ring stabilization energies. 64 The stacking interactions occurred in different systems were analyzed, for example, between non-RAHB rings (particularly (i) two planar five-membered hydrogen-bridged rings 64 and (ii) planar sixmembered hydrogen-bridged rings and C 6 -aromattc rings 69 ) and RAHB rings ((iii) two six-membered RAHB rings 70 and (iv) six-membered RAHB rings and C 6 -aromatic rings 71 ). In these studies, the authors demonstrated that the stacking interactions between two six-membered RAHB rings (−4.7 kcal mol −1 ) and the stacking interaction between the sixmembered RAHB ring and C 6 -aromatic rings (−3.7 kcal mol −1 ) were more robust than the normal benzene•••benzene stacking interaction (−2.7 kcal mol −1 ).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Several studies suggested that important and strong stacking interactions can be formed between aromatic and nonaromatic molecules or fragments or between two nonaromatic moieties . Most recently, the research on amyloids, that are considered responsible for Alzheimer's disease, showed that aromatic–aliphatic interactions are of greater importance than aromatic–aromatic interactions in amyloid‐β polypeptides .…”
Section: Introductionmentioning
confidence: 99%